Biobank Establishment and Sample Management in the Tohoku Medical Megabank Project - Minegishi, Naoko; Nishijima, Ichiko; Nobukuni, Takahiro; Kudo, Hisaaki; Ishida, Noriko; Terakawa, Takahiro; Kumada, Kazuki; Yamashita, Riu; Katsuoka, Fumiki; Ogishima, Soichi; Suzuki, Kichiya; Sasaki, Makoto; et al. (Tohoku journal of experimental medicine, 2019)
The Tohoku Medical Megabank biobank (TMM biobank) is the first major population-based biobank established in Japan. The TMM biobank was established based on two population cohorts and is a reconstruction program from the Great East Japan Earthquake and Tsunami of 2011. The biobank stores more than 3.4 million tubes of biospecimens and associated health and analytic data obtained from approximately 150,000 TMM cohort participants between May 2013 and December 2018, and the TMM biobank currently shares high-quality specimens and data. Various biospecimens, including peripheral and cord blood mononuclear cells, buffy coat, plasma, serum, urine, breast milk and saliva have been collected in the TMM biobank. To minimize human error and maintain the quality of data and specimens, we have been utilizing laboratory information management system into various biobank procedures from registration to storage with various automation systems, such as liquid dispensing, DNA extraction and their storage. The biobank procedures for the quality management system (ISO 9001:2015) and information security management system (ISO 27001:2013) are certified by the International Organization for Standardization. The quality of our biobank samples fulfills the pre-analytical requirements for researchers conducting next-generation whole genome sequencing, DNA array analyses, proteomics, metabolomics, etc. We established analytical centers to conduct standard genomic and multiomic analyses in-house and share the generated data. Additionally, we generate thousands of Epstein-Barr virus (EBV)-transformed lymphoblastoid cell lines and proliferating T cells for functional studies. The TMM biobank serves as an indispensable infrastructure for academic, clinical and industrial research to actualize next-generation medicine in Japan.